THE ROLE OF MANAGEMENT ACCOUNTING IN STRATEGIC DECISION-MAKING FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Cristino Gusmao (Count : Journal of Accounting, Business and Management, 2025)
This study aims to examine the role of management accounting in supporting strategic decision-making within Micro, Small, and Medium Enterprises (MSMEs), particularly in the context of emerging markets. Employing a quantitative descriptive method, the research gathered data through structured questionnaires distributed to 75 respondents from five MSMEs. The data were analyzed using descriptive statistics and regression analysis. Results reveal that although MSMEs frequently utilize basic accounting tools such as budgeting and cost tracking, the adoption of more advanced practices like forecasting and variance analysis remains limited. Businesses that integrate management accounting more consistently report higher strategic clarity, cost efficiency, and investment readiness. The study contributes a novel perspective by focusing on informal and partial adoption of accounting tools, demonstrating that even limited use can provide significant strategic value. Unlike previous studies that emphasize full-scale systems, this research highlights the practical realities of small enterprises operating with constrained resources. It also identifies key barriers such as low financial literacy, lack of access to technology, and overreliance on intuitive decision-making. By offering a contextualized framework tailored to the needs and capabilities of MSMEs, the research adds depth to the existing literature and offers policy-relevant insights for stakeholders seeking to enhance MSME performance. In conclusion, management accounting—when appropriately adapted—can function as a vital strategic tool for MSMEs, supporting sustainable growth and competitiveness in dynamic economic environments.